Production traits in Egyptian water buffaloes and Mpwapwa cattle - Katyega, P.M.J. (1981)
The reproductive and productive performances of buffaloes and Mpwapwa cattle raised under similar conditions in central Tanzania are investigated. Comparisons and data on age at first calving, calving interval, sex ratio, birth and weaning weights, growth rate, milk production and butter fat yield of both species provided.